Hubungan Aktivitas Fisik dalam Mengontrol Kadar Gula Darah pada Pasien Diabetes Melitus di Puskesmas Jati Makmur Kota Binjai Tahun 2021 - Nevy Setyaning Rahayu; Amaliah Stia Sundari; Maraiman Rambe; Nur Syifa Fadhilah; Tantri Sriedelina Sigalingging; Tiarnida Nababan (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
AbstractDiabetes mellitus (DM) is explained as a group of metabolic diseases indicated by an increase occuring in blood glucose level which is termed "hyperglycemia", and its trigger is resulted from a defect in insulin secretion, insulin activity, and even both of them. In general, the incidence of diabetes mellitus is influenced by a lack of exercise or activity. Physical activity has a strong influence on energy balance and can be perceived as the prominent factor which is capable of converting blood sugar levels into energy. This study aimed at determining the relationship of physical activity in controlling blood sugar levels in DM patients at Jati Makmur Health Center Binjai. The researcher utilized a descriptive analytic method and applied a cross sectional approach. The population comprised 86 respondents. A total sampling technique was employed in this study, and it encompassed 86 samples. The data collected in this study were attained by utilizing GPAQ. and the data analysis the researchers applied was the Chi-square test. The results demonstrated that p = 0,001 < alpha value of 0,05, showing that Ha is accepted. To sum up, the relationship of physical activity in controlling blood sugar levels in DM at Jati Makmur Health Center Binjai City was found. Keywords : physical activity, diabetes mellitus, blood sugar levels